FINANCIAL PERFORMANCE: THE ROLE OF GOOD CORPORATE GOVERNANCE (CASE STUDY IN THE MANUFACTURING COMPANIES OF BASIC AND CHEMICAL INDUSTRIAL SECTORS REGISTERED ON THE INDONESIA STOCK EXCHANGE 2016-2018) - Ari Susanti; Sri Lestari (Fakultas Bisnis, 2020)
This study aims to examine the effect of implementing good corporate governance as measured by an independent board of commissioners, board of directors, and audit committee on financial performance measured using Return of Equity (ROE). This research uses quantitative research. The population in this study are manufacturing companies in the basic and chemical industry sectors that consistently publish financial reports on the Indonesia Stock Exchange from 2016 to 2018. Based on the purposive sampling method, a sample of 11 companies is obtained each year to obtain 33 observational data. The data in this study use warpPLS 6.0 software. The results of this study indicate that the independent board of commissioners, the board of directors affect the financial performance, while the audit committee has no effect on financial performance.